2012
DOI: 10.1007/s00204-012-0893-4
|View full text |Cite
|
Sign up to set email alerts
|

S-Mercuration of rat sorbitol dehydrogenase by methylmercury causes its aggregation and the release of the zinc ion from the active site

Abstract: We previously developed a screening method to identify proteins that undergo aggregation through S-mercuration by methylmercury (MeHg) and found that rat arginase I is a target protein for MeHg (Kanda et al. in Arch Toxicol 82:803-808, 2008). In the present study, we characterized another S-mercurated protein from a rat hepatic preparation that has a subunit mass of 42 kDa, thereby facilitating its aggregation. Two-dimensional SDS-polyacrylamide gel electrophoresis and subsequent peptide mass fingerprinting us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In the experiments that we investigated the effect of MeHg on hepatic arginase I described above, we coincidentally detected other proteins in the same hepatic preparations that also readily underwent covalent modifi cation by MeHg and subsequently became aggregated (Kanda et al, 2012). The rat hepatic preparation was incubated with different concentrations of MeHg (1-200 μM) at 37°C for 1 hr, and then each mixture was centrifuged at 12,000 × g for 10 min.…”
Section: Sorbitol Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…In the experiments that we investigated the effect of MeHg on hepatic arginase I described above, we coincidentally detected other proteins in the same hepatic preparations that also readily underwent covalent modifi cation by MeHg and subsequently became aggregated (Kanda et al, 2012). The rat hepatic preparation was incubated with different concentrations of MeHg (1-200 μM) at 37°C for 1 hr, and then each mixture was centrifuged at 12,000 × g for 10 min.…”
Section: Sorbitol Dehydrogenasementioning
confidence: 99%
“…The lane numbers 1, 2, 3, 4, and 5 correspond to MeHg concentrations of 0, 1, 10, 100, and 200 μM, respectively. Reprinted from Kanda et al, 2012. The assay was used to detect BPM-modifi ed thiols in proteins that had been exposed to MeHg.…”
Section: Figmentioning
confidence: 99%
“…Two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis was used to separate the protein, and it was identified by peptide mass fingerprinting using matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF/MS). This 42 kDa protein was identified as sorbitol dehydrogenase (SDH) [19]. Using recombinant rat SDH possessing 10 cysteine residues in a subunit [20], we found that MeHg was covalently bound to SDH through Cys44, Cys119, Cys129, and Cys164, resulting in the inhibition of its catalytic activity and the release of zinc ions, facilitating protein aggregation [19].…”
Section: S-mercuration Of Proteins By Mehgmentioning
confidence: 99%
“…High levels of MeHg target proteins such as tubulin and a disintegrin and metalloproteinases (Imura et al, 1980;Wasteneys et al, 1988;Tamm et al, 2008). We also found that MeHg inactivates neuronal nitric oxide synthase, sorbitol dehydrogenase and arginase-I through S-mercuration of these proteins (Shinyashiki et al, 1998;Kanda et al, 2012Kanda et al, , 2008. We therefore hypothesize that an approach to detect electrophilic modification of proteins by MeHg is required for understanding the toxicity or health effects of MeHg.…”
Section: Introductionmentioning
confidence: 82%